New records and modeling potential distribution of Plestiodon tamdaoensis (Bourret, 1937) and Scincella devorator (Darevsky, Orlov & Ho, 2004) in Vietnam (Scincidae) - Anh Van Pham; Anh Tuan Nguyen; Anh Minh Hoang Nguyen; Linh Thuy Thi Dao; Chi Ha Thi Tran; Minh Duc Le; Truong Quang Nguyen (Herpetozoa)
The Vietnam Skink (Plestiodon tamdaoensis) was described from Tam Dao National Park, Vietnam, in 1937, and the species is currently known only from northern Vietnam and Hong Kong of China, whereas the Devouring Forest Skink (Scincella devorator) was described from Yen Tu Nature Reserve, Vietnam, in 2004, and the species is endemic to northern Vietnam. As a result of our field surveys in 2023 and 2024 in Ba Vi National Park, Vietnam, we reported new distribution records, morphological data, and natural history of Plestiodon tamdaoensis and Scincella devorator. In addition, we used species distribution modeling to predict the potential distribution of these species. The model showed that the potential distribution of P. tamdaoensis is approximately 110,000 km2 and that of S. devorator is approximately 130,000 km2, covering northern Vietnam, southern China, and northern Laos, significantly expanding its known range compared to the IUCN range map.